The internal friction and phase transition of solid oxygen - Erenburg, A.I.; Leont’eva, A.V.; Varyukhin, V.N.; Marinin, G.A.; Prokhorov, A.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We report an experimental study of the low frequency internal friction (LTIF) in solid oxygen in temperature range 7–52 K. Comparison of the temperature dependence of IF with data of x-ray diffraction and other thermodynamic and elastic properties, shows that anomalies of temperature dependence of the internal friction are resulted from phase transitions in solid oxygen.